Analysis of the local energy potential connection with power plants based on archimedes turbine 10 kW - Yosi Apriani; Zulkiffli Saleh; Riyan Kurnia Dillah; Ian Mochamad Sofian (Journal of Robotics and Control (JRC), 2020)
Research on the availability of water potential for the development of power plants with various scales and types of power plants has been done. Since most existing water sources have small discharges and low heads, this study aimed at designing a micro-hydropower center as one of the ways the electrical energy crisis could be avoided, with one of the renewable energy potentials, namely the potential energy of water in Micro Hydro Power Plant. Further studies were related to water resources to Micro Hydro Power Plants (MHPP) construction, especially Archimedes screw turbines guide parameters that corresponded to flow velocity, channel cross-section, and flow volume. It aimed to connect the local energy potential to the output power of the Archimedes screw turbine. The methods used for this study were 1. Observation 2. Data collection, and 3. Data Analysis. The study was carried out using an observation method that adopted field data collection techniques assisted by measuring equipment to collect data coverage that refers to related parameters. The power available on the channel resulted was 946 kW, and the power generated in the turbine was 5.9 kW.